Effect of Gold Nanoparticles in Microbial Fuel Cells Based on Polypyrrole-Modified Saccharomyces cerevisiae - Kasparas Kižys; Domas Pirštelis; Inga Morkvėnaitė-Vilkončienė (Biosensors)
Microbial fuel cells (MFCs) are a candidate for green energy sources due to microbes’ ability to generate charge in their metabolic processes. The main problem in MFCs is slow charge transfer between microorganisms and electrodes. Several methods to improve charge transfer have been used until now: modification of microorganisms by conductive polymers, use of lipophilic mediators, and conductive nanomaterials. We created an MFC with a graphite anode, covering it with 9,10-phenatrenequinone and polypyrrole-modified Saccharomyces cerevisiae with and without 10 nm sphere gold nanoparticles. The MFC was evaluated using cyclic voltammetry and power density measurements. The peak current from cyclic voltammetry measurements increased from 3.76 mA/cm2 to 5.01 mA/cm2 with bare and polypyrrole-modified yeast, respectively. The MFC with polypyrrole- and nanoparticle-modified yeast reached a maximum power density of 150 mW/m2 in PBS with 20 mM Fe(III) and 20 mM glucose, using a load of 10 kΩ. The same MFC with the same load in wastewater reached 179.2 mW/m2. These results suggest that this MFC configuration can be used to improve charge transfer.